Beneficial effects of intramyocardial mesenchymal stem cells and VEGF165 plasmid injection in rats with furazolidone induced dilated cardiomyopathy. Issue 8 (5th March 2015) - Yu, Qin; Fang, Weiyi; Zhu, Ning; Zheng, Xiaoqun; Na, Rongmei; Liu, Baiting; Meng, Lili; Li, Zhu; Li, Qianxiao; Li, Xiaofei
Abstract To explore the impact of myocardial injection of mesenchymal stem cells (MSCs) and specific recombinant human VEGF165 (hVEGF165) plasmid on collagen remodelling in rats with furazolidone induced dilated cardiomyopathy (DCM). DCM was induced by furazolidone (0.3 mg/bodyweight (g)/day per gavage for 8 weeks). Rats were then divided into four groups: (i) PBS group (n = 18): rats received equal volume myocardial PBS injection; (ii) MSCs group (n = 17): 100 μl culture medium containing 105 MSCs were injected into four sites of left ventricular free wall (25 μl per site); (iii) GENE group (n = 18): pCMVen‐MLC2v‐EGFP‐VEGF165 plasmid [5 × 109 pfu (0.2 ml)] were injected into four sites of left ventricular free wall (0.05 ml per site)] and (iv) MSCs+GENE group (n = 17): rats received both myocardial MSCs and pCMVen‐MLC2v‐EGFP‐VEGF165 plasmid injections. After 4 weeks, cardiac function was evaluated by echocardiography. Myocardial mRNA expressions of type I, type III collagen and transforming growth factor (TGF)‐β1 were detected by RT‐PCR. The protein expression of hVEGF165 was determined by Western blot. Myocardial protein expression of hVEGF165 was demonstrated in GENE and MSCs+GENE groups. Cardiac function was improved in MSCs, GENE and MSCs+GENE groups. Collagen volume fraction was significantly reduced and myocardial TGF‐β1 mRNA expression significantly down‐regulated in both GENE and MSCs+GENE groups, collagen type I/III ratio reduction was more significant in MSCs+GENE group than in MSCs or GENE group. Myocardial MSCs and hVEGF165 plasmid injection improves cardiac function possibly through down‐regulating myocardial TGF‐β1 expression and reducing the type I/III collagen ratio in this DCM rat model.